There was this question where it was given that $a_n > 0$ and $s_n = a_0 + a_1 + a_2 +..........+a_n$ and here I was to prove that if : $\sum a_n$ converges/diverges so does $\sum {a_n/s_n}$ converge/diverge likewise ;

Now here was how I approached it : consider that I am trying to prove that $\sum {a_n/s_n}$ is converging then say I am trying to prove that $\lim_{n \to \infty} [({a_n/s_n})/({a_{n-1}/s_{n-1}})] <1$ which is equivalent to $\lim_{n \to \infty} (a_n* s_{n-1})/\lim_{n \to \infty} (s_{n}*a_{n-1})$, now since we already know that $a_n$ is converging we can say that $\lim_{n \to \infty} a_n = 0$ thus using this we can say that the ratio $\lim_{n \to \infty} (a_n* s_{n-1})/\lim_{n \to \infty} (s_{n}*a_{n-1}) = 0$ but in the denominator too we have $\lim_{n \to \infty} a_{n-1}$ which too tends to $0$ as $\lim_{n \to \infty} a_n = 0$ and then we have $0/0$ which is absurd, so I abandoned this method.

Can anyone modify by method above or was it really of no great use ?

The second method I approached it was by trying to prove that the ratio $a_n/({a_n/s_n})$ is positive and finite which if proved then $\sum a_n$ and $\sum {a_n/s_n}$ would converge or diverge together. Now if $\sum a_n = s_n$ was converging then it's done but if $\sum a_n$ were diverging then that would really unsettle this method since in $a_n/s_n, s_n = \sum a_n$ and $\sum_{n = o}^{n = \infty} a_n = \infty$, again I would get the ratio $a_n/s_n = 0$ and thus I turn to here.

Was there any mistake in my approach above ? And could it be modified ?or just could anyone suggest me a better approach ?


Lemma: Suppose $0< b_n <1$ for all $n.$ Then $\prod_n b_n > 0 \iff \sum_n (1-b_n) < \infty.$

Suppose $s_n \to \infty.$ Summing over $n>1,$ we have

$$\sum a_n/s_n = \sum (s_n-s_{n-1})/s_n = \sum (1-[s_{n-1}/s_n]).$$

If this sum converges, then by the lemma,

$$\frac{s_1}{s_2} \frac{s_2}{s_3}\cdots \frac{s_{n-1}}{s_n} = \frac{s_1}{s_n} \to L > 0.$$

That's a contradition, so $\sum a_n/s_n = \infty.$

  • 1
    $\begingroup$ the lemma you stated above ,just could a cite source where I can look upon it $\endgroup$ – Arnav Das Oct 26 '15 at 7:36

Note that we have:

$$\frac{a_n}{s_n}=\frac{s_n-s_{n-1}}{s_n}\leq \int_{s_{n-1}}^{s_n}\frac{dt}{t}\leq \frac{s_n-s_{n-1}}{s_{n-1}}=\frac{a_n}{s_{n-1}}$$

1) Suppose first that your series $\displaystyle\sum a_n$ is convergent. Then there exists $L$ such that $s_n\leq L$ for all $n$. By the above, we get for all $N$ that $$\sum_{n=1}^{N}\frac{s_n-s_{n-1}}{s_n} \leq \int_{s_{0}}^{s_N}\frac{dt}{t}\leq \int_{s_0}^{L}\frac{dt}{t}$$

Hence the series $\displaystyle \sum \frac{a_n}{s_n}$ is convergent.

2) Suppose now that the series $\displaystyle \sum a_n$ is divergent. If $\displaystyle \frac{a_n}{s_n}$ does not $\to 0$, the series $\displaystyle \sum \frac{a_n}{s_n}$ is divergent. If $\displaystyle \frac{a_n}{s_n} \to 0$, there exists $K$ such that $n\geq K$ imply $\displaystyle s_n-s_{n-1}=a_n\leq \frac{s_n}{2}$. This imply $s_n\leq 2s_{n-1}$, and then $$\frac{s_n-s_{n-1}}{s_n}\geq \frac{1}{2}\frac{s_n-s_{n-1}}{s_{n-1}}$$ Now use the second inequality with the integral to finish.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.